MARKETING RESEARCH OF STUDENTS' ATTITUDE TO ORGANIC FOOD (INNOVATIVE ECONOMY, 2020)
Penkova O.H., Kharenko A.O., Lementovska V.A. MARKETING RESEARCH OF STUDENTS' ATTITUDE TO ORGANIC FOODPurpose. The aim of the article is identification and ranking of factors that determine the attitude of the student segment of consumers to organic food.Research methodology. The article uses general scientific and marketing research methods. In particular, systematic analysis and a comprehensive approach, as well as methods of collecting qualitative data such as focus groups and in-depth interviews, are used to identify the factors that determine the attitude of the student segment of consumers to organic food. Ranking of factors is performed by collecting quantitative data by questionnaires and processing the results by the arithmetic weighted average.Findings. The list of the main factors that potentially influence the attitude of student youth to organic food is determined. Using a questionnaire survey, the strength of the influence of individual factors on the desire to purchase organic food is assessed using a hierarchical rating scale. It is found that the vast majority of respondents determined the price and income level as the most significant factors.Confidence in the “organic” of products is the third most important in the decision to purchase organic food, which is determined by domestic specifics, namely the presence on the market of counterfeit products of unscrupulous producers. It has been established that the factors of concern for one's own health and ecology, which are of paramount importance for consumers in the developed countries of the world, are of secondary importance for the surveyed student youth. It is stated that domestic producers of organic food to successfully promote their products in this market segment need to adjust their own marketing systems.Originality. The main factors that define the attitude to organic food of the student segment of consumers and their hierarchical ranking depending on the strength of influence are determined.Practical value. The identified main factors influencing the formation of students' attitudes to organic food allow domestic producers to adjust the marketing mix for this segment of consumers.Key words: organic food products, student segment of consumers, attitude to organic products, motives of consumer behaviour, hierarchy of factors.
Keywords: Key words; organic food products; student segment of consumers; attitude to organic products; motives of consumer behaviour; hierarchy of factors.